A COMPREHENSIVE ABOUT THE PART OF SPEECH USING MIND MAPPING ATSTUDENTS OF2017A STKIP PGRI JOMBANG - Chilyatus Sariroh (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2019)
We present an implementation about mind mapping learning of part of speech on direct explanation using mind mapping to the students. This research aims to share the knowledge about learning part of speech using mind mapping and also to know the students’ comprehension ability about it. So that student can understand its function of each part of speech by using simple learning of mind mapping. This study was carried out among 20 students ofSTKIP PGRI Jombang especially in English Department. This study was descriptive and applied qualitative research method. The results show that 25% student have a very good comprehension and 50% have good comprehension20%have an enough comprehension and the last 5% are having low comprehension about part of speech (n=20). Part of speech is one of grammar factor that very important basic to understand the whole next grammar. Therefore, we need to share the explanation clearly and simple to the students who still don’t understand. In conclusion, the students’ comprehension in grammar about part of speech using mind mapping were categorized into “good comprehensive” category. However, based on these results, we have managed to put forward a number of recommendation and suggestion.